旧体式下的新面貌：鲍照乐府诗的承变: Bao Zhao’s Inheritance and Innovation in Yuefu Poetry - Kock Si Jie 郭思捷 (Journal of Sinological Studies 漢學研究學刊, 2024)
鲍照（约414-466）最为人称道的是其拟、代乐府诗，尤以《拟行路难》最为学界所关注。此组诗沿用旧有曲题，同时亦运用时人视为“体小而俗”的七言、杂言体进行创作，并且开创隔句用韵的方式，成功开辟出富有抒情张力的新体式，对文学体式的革新与发展具积极意义。然，值得一提的是，与《拟行路难》同属乐府诗范畴的“代”乐府，占现存诗作的多数，却较少被深入探究。论者多聚焦于其抒情特质及题名“代”之意涵，虽其内容大多承续汉魏以来游子思妇、香草美人等主题，然若从“文体”角度观之，实可窥见其对乐府传统体式的承接与创变。是以，本文将鲍照所有乐府诗纳入考察范围，尝试以“承继”与“新变”为研究视角，探讨其在体式层面对传统体裁、题材与体貌的赓续与转化，并进一步揭示其所构建的另一种乐府体式风貌。 Bao Zhao (CE 414-466) is best known for his imitative (Ni) and persona (Dai) yuefu poems, with scholarly attention primarily focused on the Ni Xinglu Nan (Imitation of “The Lament of the Road”). These poems retain traditional yuefu titles while adopting poetic forms—such as seven-syllable and mixed-meter lines—often seen by contemporaries as “minor” or “vulgar.” Bao Zhao’s use of alternate-line rhyming, instead of rhyming every line, introduced a new style of heightened lyrical tension. These innovations significantly advanced the development of literary form in early medieval China. Although the Dai yuefu poems make up the bulk of Bao Zhao’s extant yuefu, they have received relatively little scholarly attention. Existing scholarship largely centers on their lyrical features or on readings of dai (persona) as a mode of “speaking on behalf of another,” often emphasizing inherited Han and Wei motifs such as the absent traveler, the longing woman, and the fragrant beauty. Yet viewed through the lens of literary form, these poems reveal a dynamic interplay of continuity and innovation within the yuefu tradition. This article examines the full corpus of Bao Zhao’s yuefu through the dual lens of inheritance and innovation, tracing his engagement with traditional forms, themes, and styles, and his transformation of them into a distinct yuefu mode. In doing so, it sheds light on his role in reshaping the formal horizons of the yuefu poetry tradition.